2022
DOI: 10.3390/diagnostics12071654
|View full text |Cite
|
Sign up to set email alerts
|

Microbiological Profiles of Patients with Periprosthetic Joint Infection of the Hip or Knee

Abstract: Periprosthetic joint infections (PJI) are one of the most devastating consequences after total joint arthroplasty. We sought to analyze the causative pathogens of patients with PJI to get better insights and improve treatment. We performed a retrospective study of all patients with PJI of the hip and knee with microbiological detection of a causative pathogen at a tertiary endoprothetic referral center between January 2016 and March 2021. A total of 432 cases with PJI (hip: n = 250; knee: n = 182) were include… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…The clinical significance of this finding is unclear, as periprosthetic infections from M. luteus are relatively rare. 18 …”
Section: Discussionmentioning
confidence: 99%
“…The clinical significance of this finding is unclear, as periprosthetic infections from M. luteus are relatively rare. 18 …”
Section: Discussionmentioning
confidence: 99%
“…Although previous studies have shown that Gram-positive cocci are the most frequently detected pathogens in patients with PJI, the literature is not consistent regarding the role of S. aureus and coagulase-negative staphylococci [ 3 , 12 ]. While Tsai et al identified S. aureus as the most common pathogen with a detection rate of 26%, more recent studies by Hu et al and Stevoska et al identified coagulase-negative staphylococci with detection rates of 38.1 to 56.6% as more common [ 12 , 15 , 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…While Bjerke-Kroll et al could not detect a difference in the identified species in patients with PJI of the hip or knee, Stevoska et al described a significantly higher rate of Gram-negative bacteria in patients with PJI of the hip [ 14 , 17 ]. As our previous studies did not detect an overall difference in causative pathogens between patients with PJI of the hip and the knee, we did not evaluate this topic [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations